2017
DOI: 10.4314/ahs.v16i4.38
|View full text |Cite
|
Sign up to set email alerts
|

An anatomical and osteometric study of the femoral sulcus angle in adult Malawians

Abstract: Background: Femoral sulcus angle is particularly important in clinical evaluation of patellofemoral joint. Individuals show considerable differences in asymmetrical dimensions of the femur. Objectives: To determine the size of femoral sulcus angles in adult black Malawians using the skeletal collection in the department of Anatomy, College of Medicine and assess their gender differences; to compare femoral sulcus angles of Malawians with other ethnic groups. Methods: A cross sectional study was done in which f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
6
4
0
Order By: Relevance
“…A recent study that used similar measurement methods as those in our study showed an angle of 140.7 ± 4.4° for 45° lexion, which is similar to the angle observed in our study (143.4 ± 6.5°) [10]. In addition, values similar to previous studies was found in lexion angle at which sulcus angle was measured in this study [7,10,24]. A high sulcus angle indicates shallow or dysplastic trochlea and is observed in the majority of patients sufering from PF disorders [7,9].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A recent study that used similar measurement methods as those in our study showed an angle of 140.7 ± 4.4° for 45° lexion, which is similar to the angle observed in our study (143.4 ± 6.5°) [10]. In addition, values similar to previous studies was found in lexion angle at which sulcus angle was measured in this study [7,10,24]. A high sulcus angle indicates shallow or dysplastic trochlea and is observed in the majority of patients sufering from PF disorders [7,9].…”
Section: Discussionsupporting
confidence: 91%
“…Genderspeciic diferences in the sulcus angle and height except at the 30° lexion were identiied. These results conlict with those of previous studies [23,24,27]. Mwakikunga et al showed that there was no signiicant diference in the mean femoral sulcus angle between men and women [24].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These figures are close to those obtained by Murshed et al in a dry bone study in a Turkish population, who found an average sulcus angle of 141.2 0[10]. Mwakikunga et al, in an osteological study in a Malawian population found a mean angle of 142.4 0[11], which is close to the figures obtained in the current study. A study on normal Chinese subjects using 3D CT images reported a mean angle of 154.41 0[12].…”
supporting
confidence: 92%